Empowerment of Youth Organization Through Sublimation Screen Printing Training and Product Marketing Strategies in Bahorok District, Langkat Regency - Marpaung, Nicholas; Siregar, Onan M; Safrin, Feby Aulia (Talenta Publisher, 2023)
The government shows its seriousness in developing the creative economy sector to support the economy. Fashion as a part of the creative economy today can not only be worked on by people who live in urban areas but also people who live in villages, especially with the even distribution and growth of information technology in the country. People who live in the village do not always have to be farmers or workers in the agrarian sector, but also have to have job options that can be a lifestyle to continue to show their existence even though they are from the village, especially young people who choose to stay in the village. Through this service, we will provide screen printing and digital printing training, as well as provide all information about the potential and opportunities of this kind of business to young people in Bahorok Village, Bahorok District, Langkat Regency. By understanding printing techniques digitally, it is hoped that it will be able to facilitate printing in larger quantities, and of course will provide better economic benefits as well. We will also involve speakers and business actors who have succeeded in this screen printing business so that participants can directly deal with business actors and get more in-depth experience and training. In the future, further service is needed which will be focused on better marketing strategies to continue to support this sustainable and effective service activity.